Hukum Inseminasi Buatan dan Bayi Tabung serta Implementasinya - Kholilulloh, Habib; Qomari, Nur; Musthofa, Khoirul; Rusli, Rusli; Basaiban, Kasuwi; Mubin, Ufuqil (ANWARUL, 2023)
This paper aims to examine the In Vitro Fertilization (IVF) program from the perspective of Islamic law, and positive law in Indonesia, so that it is clear whether the practice of IVF is religious or Indonesian law. In conducting the analysis, the authors use a type of qualitative literature research with a normative approach. The results of this paper are: (1) The artificial insemination program for IVF is permitted in Islamic law, with the condition that the sperm must come from the husband himself. In vitro insemination with the Surrogate Mother's uterus rental model, there are two opinions. The first opinion states that surrogacy is prohibited because it creates a mix of lineages which are also related to mahram and inheritance. The second opinion states that Surrogate Mother is allowed for emergency reasons. (2) Implementation of IVF in Indonesia is regulated in Law Number 36 of 2009 concerning Health. The law regulates the conditions and procedures that must be met to be able to participate in the program so that babies born in the program do not violate ethics in society and religion.